Long-term care reform in Germany – at long last. (2019) - Link, S.
Abstract: Demographic and societal changes make it more and more indispensable to protect against the risk of care costs surpassing a person's financial means. Nevertheless, only few governments have acted to create public funding systems that, if existent at all, usually only cover part of the expenses for elder care. Long-term care insurance (LTCI) is designed to fund basic care needs in later life, such as washing and dressing. Regardless of where individuals receive this support in old age, how it is funded is a growing issue. In many countries, people may augment their compulsory state system with private policies available from insurance companies. In Germany, a well-established public system that underwent major reforms exists. From 2017 onwards, a completely new care definition and assessment process replaced the former ones. Two major changes constitute the reform: First, when evaluating the need for care, the former focus on estimating the length of time required for care was replaced by the determination of the degree of independence. Second, cognitive impairments will be acknowledged more adequately than in the past, where the focus was on physical abilities. Furthermore, the contribution to be paid by the care recipient in a nursing home will no longer be dependent on the severity of the care need. In Germany, private LTC products used a combination of the social security definition, an ADL-based trigger and a dementia trigger until the end of 2016. Thus, the reform has repercussions for the local private insurance industry. What would happen to in-force business, how a new benefit trigger should look like, how old and new definition compare and how pricing rates can be derived were only some of the questions that had to be answered in advance. The reform could point the way for future public schemes and private policies elsewhere. Which questions had to be answered and what issues had to be solved in advance, together with lessons learned during and shortly after the reform was undertaken, can serve as an accompaniment for the introduction or reform of public LTC schemes and for the local insurance industry in other countries.